The MAVERIC Survey: Dynamical Origin of Radio Sources in Galactic Globular Clusters - Zhao, Y.; Heinke, C.O.; Shishkovsky, L.; Strader, J.; Chomiuk, L.; Maccarone, T.J.; Bahramian, Arash; Sivakoff, G.R.; Miller-Jones, James; Tremou, E. (IOP PUBLISHING LTD, 2021)
We investigate potential correlations between radio source counts (after background corrections) of 22 Galactic globular clusters (GCs) from the MAVERIC survey and the stellar encounter rates (Γ) and masses (M) of the GCs. Applying a radio luminosity limit of Llim = 5.0 × 1027, erg, s-1, we take a census of radio sources in the core and those within the half-light radius of each cluster. By following a maximum likelihood method and adopting a simplified linear model, we find an unambiguous dependence of core radio source counts on Γ and/or M at 90% confidence, but no clear dependence of source counts within the half-light radius on either Γ or M. Five of the identified radio sources in GC cores above our adopted limit are millisecond pulsars or neutron star X-ray binaries, the dependence of which on Γ is well known, but another is a published black hole (BH) X-ray binary candidate, and 10 others are not identified. Accounting for these verified cluster members increases the significance of the correlation with M and/or Γ (to 99% confidence) for fits to core and half-light region source counts, while excluding a dependence on Γ alone at 90% (core) and 68% (half-light) confidence. This is consistent with published dynamical simulations of GC BH interactions that argue Γ will be a poor predictor of the distribution of accreting BHs in GCs. Future multiwavelength follow-up to verify cluster membership will enable stronger constraints on the dependence of radio source classes on cluster properties, promising a new view on the dynamics of BHs in GCs.